Challenges of applying the contract integrated project delivery method in construction industry projects based on the knowledge-intensive service. (9th March 2023) - Jahroudi, Mohammadjavad Nasiri; Nani, Mehdi; Safa, Ebrahim; Sadeh, Ehsan
In the present paper, an attempt has been made to identify the principles of the integrated project delivery (IPD) contract method, to assess the current status of infrastructure projects in developing countries to implement these principles. For this purpose, using a mixed method (qualitative and quantitative) and using interview tools and questionnaires, the opinions of experts in road construction projects in Iran were collected. The results of evaluating the current situation of these projects showed that in recent years, the application of participatory approaches, which is the beginning of IPD-based projects, is moving from the path of philosophy to the method of implementation. But there is still a long way to go to reach the end of the road, which is to complete projects with the IPD system. Also, based on the opinions of experts in examining the requirements and prerequisites for achieving the principles of IPD, various challenges were identified. Then, using integrated fuzzy multi-criteria decision-making methods (FAHP and FTOPSIS), these challenges were prioritised and corrective solutions for more important challenges were proposed.